ASUPAN MAKANAN ANAK BALITA DI DESA TANJUNG TANAH KECAMATAN DANAU KERINCI KABUPATEN KERINCI PROVINSI JAMBI - Harmupeka, Apridanti; Fridayati, Lucy; Yuliana, Yuliana (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
The purpose of this research is to describe the intake of food children (1-5 years) which includes a menu, frequency, portion, and how to give the food. The method of this research is descriptive with qualitative data. The informant on this research are mothers who have children (1-5 yerars) and total the informants was determined with Snowball sampling method. The method to get information are observation, interview and documentation process. the results showed that the intake of food who children at Tanjung Tanah, Danau Ketinci subdistrct, Kerinci regency, Jambi province, based the indicator menu of food children which not refer to B2SA (diverse, nutritious, balance and safe). Based the indicator portion, portion, the portion of rice and vegetable not in appropriate to the advice DepKes RI. The next indicator is based on the food who children (1-5 years), not in accordance with the recommendation DepKes RI and the based on food frequency indicator, was refer to the recommendation DepKes RI.Keyword : Food Supply, Children (1-5 years), Tanjung Tanah Village